2018
DOI: 10.1021/acs.biomac.8b00414
|View full text |Cite|
|
Sign up to set email alerts
|

Luminescent Gold Nanocluster-Decorated Polymeric Hybrid Particles with Assembly-Induced Emission

Abstract: Ultrasmall gold atom clusters (<2 nm in diameter) or gold nanoclusters exhibit emergent photonic properties (near-infrared absorption and emission) compared to larger plasmonic gold particles because of the significant quantization of their conduction band. Although single gold nanocluster properties and applications are being increasingly investigated, little is still known about their behavior and properties when assembled into suprastructures, and even fewer studies are investigating their use for biomedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
1
35
0
2
Order By: Relevance
“…The reduction in the spacing between the emitting cores hampers and even reverses the natural decrease in the fluorescence intensity that arises from heating. 50 The same fluorescence emission responses to the temperature and pH of the medium were observed for all synthesized hybrids and are in full agreement with our previous research relating to the functionalization of other types of fluorescent NPs with these kinds of multithiolated polymers. 27,53 For practical applications it is important to study the photo-/chemical stabilities of the new hybrid CuNCs to assess the degree of protection provided to the CuNCs by the polymeric coverage.…”
Section: Resultssupporting
confidence: 91%
“…The reduction in the spacing between the emitting cores hampers and even reverses the natural decrease in the fluorescence intensity that arises from heating. 50 The same fluorescence emission responses to the temperature and pH of the medium were observed for all synthesized hybrids and are in full agreement with our previous research relating to the functionalization of other types of fluorescent NPs with these kinds of multithiolated polymers. 27,53 For practical applications it is important to study the photo-/chemical stabilities of the new hybrid CuNCs to assess the degree of protection provided to the CuNCs by the polymeric coverage.…”
Section: Resultssupporting
confidence: 91%
“…The AIE phenomenon has been observed in several organic compounds of low molecular weight and in polymers [73]. The aggregation-induced luminescence of NCs has been achieved either using solvent-induced aggregation or addition of additives such as ionic polymers, proteins or peptides [74][75][76]. Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77].…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…Zhang et al reported the preparation of Au nanorods (Au NR) and PNIPAm composites with fast thermal/optical response and high heating rate by a traditional electrospinning technique presenting potential applications in smart sensors [ 97 ]. Hembury and collaborators showed a synthetic pathway that combined gold nanoclusters with thermo-sensitive diblock copolymers of poly(ethylene glycol) (PEG) and PNIPAm to form a new class of gold-polymer, micelle-forming, hybrid NP [ 98 ]. The thermo-sensitive polymers enhanced the native fluorescent signal of Au NPs.…”
Section: Biomedical Applications Of Thermal-nanomaterialsmentioning
confidence: 99%
“…( d ) Schematic representation and TEM image of Au-thermosensitive polymer (PEG-PNIPAm) nanohybrids. Reproduced with permission from [ 94 , 95 , 97 , 98 ]. Copyright American Chemical Society, 2015, 2014, 2017, 2018.…”
Section: Figures Scheme and Tablementioning
confidence: 99%